Assessment of Psychological Distress among Pregnant Women in Kirkuk City - Abbas Lateef Muhe AL-deen (College of Nursing,University of Mosul, 2014)
Background and Objective: Stress is a psychological state of fatigue or physical fatigue affects an individual in response to psychological pressure or unexpected real life. Stress can be short-term or longterm, Feeling stressed is common during pregnancy, but too much stress can make a pregnant woman uncomfortable. Stress can make trouble sleeping, headaches, loss of appetite or overeating. Some studies show that high levels of stress in pregnancy may cause certain problems during childhood. The purpose of this study was to assess the psychological distress among pregnant women's in Kirkuk city, as well as to find a relationship between psychological distress and some socio- demographic characteristics such as (No. of children, socioeconomic status, pregnancy stage, woman's age). Material and Method: A descriptive study was carried out in gynecological consultation at hospitals (Azadi teaching, general Kirkuk) in Kirkuk city, to assess the psychological distress in pregnant women for a period from the 15th of June 2013 and up to the 25th of November, 2013 to achieve the objectives of the study. A probability (purposive) sample of (120) pregnant women's. Developed questionnaire was constructed for the purpose of the study, which consisted of three parts: the demographic characteristics; medical data and assessment psychological distress among pregnant women. The data were collected through the use of the interview. They were analyzed through the application of descriptive statistical analysis (frequency , percentage) and inferential statistical (chi-square) . Results: The findings of the study indicated that (35%) were in the age group ( 22-26), and (85%) were from the urban, (30.84%) of the sample were graduate from Institute and above, (70%) of them housewife , (65.83 %) of the sample had barely sufficient monthly income. Regarding to the medical data finding of the study indicated that (57.5%) of them in the 3rd trimester , the Miscarriage in the whole study represented (75.83%) is null, (29.17) have null children, (55.83%) overweight, (94.17%) no smoking, (88.33%) have no history of chronic disease ,(79.1%) have no pregnancy induced hypertension ,(98.23%) have no pregnancy induced diabetic mellitus. Conclusions: The psychological distress in the study sample was founded in the third Trimester and founds a Significant relationship between Pregnancy Stage and Psychological Distress. Also founds a Significant relationship between socioeconomic status and Psychological Distress. As the study concluded that most of the pregnant women were to have moderate psychological distress. Keywords : Assessment ,Psychological Distress, Pregnant Women, Pregnancy, Trimesters , Miscarriage.